Recorded interviews: Oral sources, oral and sound archives and historical tensions of the present As falas gravadas pelos outros: fontes orais, arquivos orais e arquivos sonoros, inquietações da história do tempo presente - Borges V.T.* (2012)
Current essay problematizes the use by historians of interviews undertaken by other researchers and discusses the characteristics of such documents. Examples of research experiences which triggered the above concern are analyzed. Methodological issues that preoccupy present day historians are investigated. Recorded discourse, such as oral sources, oral and sound archives, made by other researchers are problematized and their potentialities and specificities are studied.